Aeschylus’ Prometheus: Regress, Progress, and the Nature of Woman - Gagarin, Michael (Hyperboreus, 2015)
One result of the changes that Aeschylus makes to Hesiod’s version of the myth of Prometheus is that the myth now emphasizes human progress as opposed to the Hesiod’s regressive view of human civilization. I examine some of the speciﬁc changes Aeschylus makes, showing how even small details contribute to the larger sense of progress. In particular, I examine the women in Prometheus Bound – those in the play (Io, the Oceanids) and others who are just mentioned. Aeschylus’ women differ greatly from Hesiod’s woman (Pandora); rather than being a threat to men, they are mostly victims (actual or potential) of men’s desire.